(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this work we examine some possible formula of authorship or dedication containing, or perhaps containing, different variants of the Iberian lexema eki-, adding some new examples to the already identified by J. de Hoz in his work Notas sobre inscripciones meridionales de la Alta Andalucía. Next, we try to establish the function of the second personal name that appears at the end of some of them, and that could correspond to the father’s name, and the conditions causing the presence of the -ki suffix in some of them.